Edukasi Perilaku Hidup Bersih dan Sehat pada Anak - Yuri Nurdiantami; Shafa Adzkia Aulia (Prisani Cendekia, 2022)
Health is fundamental aspect that should be obtained since the early phase of life. Education of Clean and Healthy Living Behavior (PHBS) is important to improve one’s health status. Kesmas Mengajar Program aim to develop further and in-depth understanding of clean and healthy living behavior in children living in sub-urban area. The program facilitates children in small group to obtain comprehensive materials as well as understanding about their personal hygiene. The program is not only focusing on theoretical based intervention but also real-life practice. Based on the pre and post test results, it is found that there are increase rate of children’s knowledge. It is sugested that another program conducted in wider scope to provide meaningful impact for the community.